(untitled) (Zaporizhzhia Historical Review, 2021)
The article considers the specificity of party and political struggle during the elections to the All-Russian Constituent Assembly in 1917. The peculiarities of organizing the electoral process are discovered, the data about the results of election campaign are cited. The author comes to a conclusion that a support given by local inhabitants to Ukrainian social parties increased substantively.